2010
DOI: 10.1186/1743-422x-7-310
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 expression on peripheral CD8+ TEM/TEMRA subsets closely correlated with HCV viral load in chronic hepatitis C patients

Abstract: BackgroundTight correlation between host circulating CD8+ T cell-mediated immune response and control of viral replication is classical characteristic of long-term HCV infection. CD8+ T cell maturation/activation markers are expected to be associated with viral replication and disease progression in chronic HCV infection. The aim of the present study was to explore novel markers on CD8+ T cells with ability to evaluate HCV viral replication and disease progression.MethodsPBMCs were isolated from 37 chronic HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 51 publications
5
29
0
Order By: Relevance
“…1A, B). Other immune cell alterations noted were in line with previous studies, including an increase in Tregs [25], a reduced frequency of pDCs [26], and a shift within the CD4 and CD8 T-cell compartments from naïve to antigen-experienced cells [27,28].…”
Section: Mait Cells Are Among the Most Severely Affected Immune Cellssupporting
confidence: 72%
“…1A, B). Other immune cell alterations noted were in line with previous studies, including an increase in Tregs [25], a reduced frequency of pDCs [26], and a shift within the CD4 and CD8 T-cell compartments from naïve to antigen-experienced cells [27,28].…”
Section: Mait Cells Are Among the Most Severely Affected Immune Cellssupporting
confidence: 72%
“…In addition to the direct effect of HCV, other factors may also enhance MDSC expansion. It is known that infection of hepatocytes by HCV could lead to inflammation in the liver and secretion of inflammatory cytokines, which can result in immune activation in chronic HCV-infected individuals [25,26]. The correlation between MDSCs and activated T cells support that inflammatory status may be an alternative mechanism for MDSC expansion in CHC patients.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to clinical markers of HCV infection, the correlation between MDSC and immunological markers was also evaluated. It is known that exposure of HCV viral antigens results in chronic immune activation that could dampen antigen-specific T cell responses and contribute to immune evasion of HCV [25,26]. The typical readout for this immune activation is detection of CD38 + activated T cells in PBMCs.…”
Section: Elevation Of Mdsc Frequency In the Peripheral Blood Of Chc Pmentioning
confidence: 99%
“…EM, effector memory. CM (7,15,16,23) in healthy volunteers as well as in clinical settings including transplantation despite the fact that these cells are lacking CCR7 expression. Indeed, the characteristics of the subsets that were identified using either CD45RA -CCR7 þ or CD45RA -CD27 þ were in sharp contrast.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there appears to have been an evolution in the subsets identified using CD45RA and CD27. While this nomenclature was pioneered as being able to identify na€ ıve, effector, and memory subsets (14), over time it has begun to be misused as a means to identify na€ ıve, central memory (CM), effector memory (EM), and T cell effector memory re-expressing CD45RA (TEMRA) populations (7,15,16). The aim of the study was to investigate the similarities and differences of the subsets identified by using three nomenclatures (CD45RA and CCR7, CD45RA and CD27, and CD45RA and CD28) in a large cohort of kidney transplant recipients with stable graft function and standard immunosuppressive regimen.…”
Section: Introductionmentioning
confidence: 99%